Supported Discharge Teams for older people in hospital acute care: a randomised controlled trial. (23rd November 2017) - Parsons, Matthew; Parsons, John; Rouse, Paul; Pillai, Avinesh; Mathieson, Sean; Parsons, Rochelle; Smith, Christine; Kenealy, Tim
Abstract: Background: Supported Discharge Teams aim to help with the transition from hospital to home, whilst reducing hospital length-of-stay. Despite their obvious attraction, the evidence remains mixed, ranging from strong support for disease-specific interventions to less favourable results for generic services. Objective: To determine whether older people referred to a Supported Discharge Team have: (i) reduced length-of-stay in hospital; (ii) reduced risk of hospital readmission; and (iii) reduced healthcare costs. Methods: Randomised controlled trial with follow-up to 6 months; 103 older women and 80 men ( n = 183) (mean age 79), in hospital, were randomised to receive either Supported Discharge Team or usual care. Home-based rehabilitation was delivered by trained Health Care Assistants up to four times a day, 7 days a week, under the guidance of registered nurses, allied health and geriatricians for up to 6 weeks. Results: Participants randomised to the Supported Discharge Team spent less time in hospital during the index admission (mean 15.7 days) in comparison to usual care (mean 21.6 days) (mean difference 5.9: 95% CI 0.6, 11.3 days: P = 0.03) and spent less time in hospital in the 6 months following discharge home. Supported discharge group costs were calculated at mean NZ10, 836 (SD NZ12, 087) compared to NZ16, 943 (SD NZ22, 303) in usual care. Conclusion: A Supported Discharge Team can provide an effective means of discharging older people home early from hospital and can make a cost-effective contribution to managing increasing demand for hospital beds.